Canards interference on the Magnus effect of a fin-stabilized spinning missile. (July 2018) - Yin, Jintao; Wu, Xiaosheng; Lei, Juanmian; Lu, Tianyu; Liu, Xiaodong
Reynolds-averaged simulations of flow over spinning finned missiles with and without canards were carried out at Ma = 0.6, 0.9, 1.5, and 2.5; α = 4°, 8°, and 12.6°; andω ¯ = 0 . 025 to investigate different mechanisms of the Magnus effect. An implicit dual-time stepping method and theγ − R e θ t transition model were combined to solve the unsteady Reynolds-averaged Navier–Stokes equations. Grid independence study was conducted, and the computed results were compared with archival experimental data. The transient and time-averaged lateral force coefficients were obtained, and the flow field structures were compared at typical rolling angles. The results indicate that in subsonic conditions, the canards interference intensifies the asymmetrical distortion of the body surface boundary layer and flow separation at different angles of attack, doubling the absolute value of the time-averaged body lateral force; the wash flow effect strengthens on the leeward tail due to the canards interference, increasing its time-averaged lateral force; in supersonic conditions, the shock and expansion waves induced by canards, the vortex system, and the flow separation are responsible for the fluctuation of the body lateral force; the direction of the canard induced wash flow alters as angle of attack increases, increasing first and then decreasing the time-averaged tail lateral force.